INTERPRETATION OF THE CONCEPT OF "CULTURAL HERITAGE" IN THE AUTHOR’S CONCEPTS - Филатьева, Татьяна (SWorldJournal, 2021)
In the article, the author examines the concept of "cultural semantics", analyzing it in the concepts of different researchers. The problem of identifying and preserving cultural heritage has become important today. Therefore, in the article, the author